Design of bifunctional synergistic NiMoO4/g-C3N4 nanocomposite for the augmentation of electrochemical water splitting and photocatalytic antibiotic degradation performances - Vijayakumar P.; Vijayan P.; Krishnan P.S.; Raja A.; Kumaravel S.; Venthan S.M.; Siva V.; Palanisamy G.; Lee J.; Afzal M. (Elsevier Ltd, 2025)
Developing cost-effective and efficient electrocatalysts across a wide pH range poses a significant challenge in electrochemical water splitting for energy generation. Designing nanocomposites with well-tuned interfaces can significantly boost electrocatalytic performance. Here, we present an effective and durable g-C3N4 (CN) modified NiMoO4 (NM) electrocatalysts coated on nickel foam (NF) for maximizing electrochemical water splitting performance. We optimized the nanocomposite for effective hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) activity in acidic, neutral, and alkaline electrolytes by adjusting the weight ratio of the g-C3N4. The NMCN-4/NF electrode exhibits the best electrochemical HER activity under alkaline and acidic conditions with lower overpotentials of ?0.114 and ?0.158 V, respectively, to achieve ?10 mA cm?2. The highest HER activity was ?127.3 mA cm?2 for the NMCN-4/NF under acidic conditions, which is 3.6 and 2.98 times greater than the pristine NM and CN-coated NF electrodes, respectively. Under an alkaline medium, the highest OER activity of the NMCN-4/NF was 152.9 mA cm?2, which is 4.07 and 2.75 folds higher than NM/NF and CN/NF electrodes, respectively. Besides, the NMCN-4 catalysts showed excellent photocatalytic degradation behavior on antibiotic pollutants with a percentage of 96.68%, which is 3.2 and 3.01% higher than pristine NM and CN catalysts, respectively. The NMCN-4 electro /photocatalysts exhibit an impressive balance of electro /photocatalytic efficiency and stability. ? 2024 Elsevier B.V.